Motywy kosmologiczne i teologiczne w "Poimandresie". Religijne przesłanie "Poimandresa" w aspekcie duchowym - Pawłowski, Kazimierz (Vox Patrum, 2025)
The subject of this paper is Poimandres, the first book of the Corpus Hermeticum. Poimandres stands out from the other books (along with book XI) in that it takes the form of a divine revelation. An essential element of this revelation are two mystical visions. The author of the paper attempts to show the spiritual meaning of these visions and to express the religious message hidden in them.